(untitled) (Quinto Sol, 2018)
An increase in affiliations to student guilds can be registered in the years prior to the University Reform. This movement supposed a mayor increase in student activities and in the organization of the student movement, which managed to transcend gremial activities. Also, this process started by the reform movement helped students to define themselves as political actors during this period. This article inquired into and reconstructed student sociability by analyzing student centers in the University of Buenos Aires with the purpose of comprehending part of the changes that this movement helped bring about on university life. In order to achieve the aims of this enquiry, student centers in the Medical, Law and Engineering Schools and the Student’s Federation, established in 1908, were taken as subjects of enquiry. The period that was analyzed spanned from the creation of these centers and associations up until 1918, when the Argentinean Student’s Federation was established as a result of the University Reform. This study focused on the different forms and models of sociability that started circulating in student centers, in a context marked by the accelerated socio-political changes that the country and the university had been experiencing throughout the first two decades of the twentieth century.